Physical Activity Level and Perspectives of Participants Transitioning from Onsite to Virtual Cardiac Rehabilitation during the Early COVID-19 Pandemic: A Mixed-Method Study - Vanzella, Lais Manata; Ghisi, Gabriela Lima de Melo; Colella, Tracey Jacqueline Fitchett; Larkin, Jillian; Vanderlei, Luiz Carlos Marques [UNESP]; Marzolini, Susan; Thomas, Scott; Oh, Paul (MDPI, 2022)
This mixed-method study aimed to compare physical activity (PA) patterns of a cross-over cardiac rehabilitation (CR) cohort with a center-based CR cohort and to explore barriers and facilitators of participants transitioning and engaging in virtual CR. It included the retrospective self-reported PA of a cross-over CR cohort (n = 75) and a matched center-based CR cohort (n = 75). Some of the participants included in the cross-over cohort (n = 12) attended semi-structured focus group sessions and results were interpreted in the context of the PRECEDE-PROCEED model. Differences between groups were not observed (p > 0.05). The center-based CR cohort increased exercise frequency (p = 0.002), duration (p = 0.007), and MET/minutes (p = 0.007) over time. The cross-over cohort increased exercise duration (p = 0.04) with no significant change in any other parameters. Analysis from focus groups revealed six overarching themes classified under predisposing factors (knowledge), enabling factors (external support, COVID-19 restrictions, mental health, personal reasons/preferences), and reinforcing factors (recommendations). These findings suggest an improvement of the PA levels of center-based CR cohort participants pre-pandemic and mitigated improvement in those who transitioned to a virtual CR early in the pandemic. Improving patients’ exercise-related knowledge, provider endorsements, and the implementation of group videoconferencing sessions could help overcome barriers to participation in virtual CR.
Keywords: cardiac rehabilitation; COVID-19; mixed methods; physical activity